2021
DOI: 10.1111/fog.12559
|View full text |Cite
|
Sign up to set email alerts
|

Migration and spawning behavior of the greater amberjack Seriola dumerili in eastern Taiwan

Abstract: Greater amberjack (Seriola dumerili) is an important fishery resource with a circumglobal distribution from tropical to temperate waters. Here, we investigated the spawning migration and habitat utilization of S. dumerili in the East China Sea (ECS). Archival tags were attached to 22 adult fish to examine their horizontal and vertical movements and estimate the spawning ground. S. dumerili were captured and released in the coastal waters of eastern Taiwan on November of 2016 and 2017.Information from seven pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
3
6
0
Order By: Relevance
“…Our findings noted that in the spring, the spatiotemporal distribution pattern of S. dumerili is higher in the southern part of the ECS, which has favorable oceanographic characteristics because of the Kuroshio Branch Current and Kuroshio Current [45]. Tone et al [46] reported that the S. dumerili spawning ground in February and March was located in the ECS. Our model predicted that in spring, catch rates would be high in the northern part of the TS, whereas in summer, these rates would increase further and the area with a high catch rate would extend toward the ECS.…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjacksupporting
confidence: 49%
See 3 more Smart Citations
“…Our findings noted that in the spring, the spatiotemporal distribution pattern of S. dumerili is higher in the southern part of the ECS, which has favorable oceanographic characteristics because of the Kuroshio Branch Current and Kuroshio Current [45]. Tone et al [46] reported that the S. dumerili spawning ground in February and March was located in the ECS. Our model predicted that in spring, catch rates would be high in the northern part of the TS, whereas in summer, these rates would increase further and the area with a high catch rate would extend toward the ECS.…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjacksupporting
confidence: 49%
“…This might be because of the availability of food and the preferred habitat-related oceanographic conditions conducive to development and survival. The mesozooplankton community in the Kuroshio region has comparable standing stock and productivity to those on the ECS shelf, indicating that sufficient food was available for the S. dumerili in this region and the warm water transported by the Kuroshio Current was optimal [46,60]. The distribution, migration, and availability of fish shoals are strongly linked to the oceanic fronts [52,61].…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjackmentioning
confidence: 98%
See 2 more Smart Citations
“…To effectively develop strategies for managing this valuable fishery resource, information on the habitat preferences of and climate-related environmental effects on the fish is required. However, although fish habitat distribution and climate-related environmental effects have been reported to be essential factors affecting fish populations, the data available on the greater amberjack population in the waters of Taiwan are almost entirely based on assessments of age and growth (Hasegawa et al, 2017;Hasegawa et al, 2020), migration, and spawning (Tone et al, 2022).…”
Section: Introductionmentioning
confidence: 99%